INDUSTRI SEPAKBOLA: PENGELOLAAN DAN AKUNTABILITAS KEUANGAN (STUDI KASUS PADA KLUB SEPAKBOLA AREMA CRONUS) - Adien Setya Suwandi; Sripujiningsih .Sripujiningsih; Sulastri Sulastri (Universitas Negeri Malang, 2017)
Football industry is a form of development of football began venturing on the economic aspect. Nowadays football is not just a sport, but rather into a business that can give an advantage. All clubs including Arema Cronus began to feel the impact of the development of the football industry that occurred in Indonesia. The most visible football industrial is the club's professional management and the commodification of football players. The purpose of this research is to understand that Arema Cronus as the industry of football, as well as understand the financial management and accountability of Arema Cronus.This research used the qualitative approach with this type of case study research. The data source is multiple resource with the technique of collecting data through observation, interview and documentation study. As a research instrument is researchers themselves (human instrument) which serves to set the focus of the research, selecting informants as a data source, perform data gathering, assessing data quality, data analysis, interpret the data and make the conclusion upon his findings. The location for this research was in office management Arema Cronus JL. Kertanegara No. 7 Malang. Analytical techniques used in this research is descriptive based on qualitative analysis.Based on the results of research, Arema Cronus is one of Indonesia's football club which has been utilizing the football business as a means to gain an advantage. Arema Cronus hold first settled towards professional management. Arema Cronus has conducted financial management so that the club management can take a decision in determining the objectives to be achieved. Financial management requires that Arema Cronus do accountability to parties with an interest in financial reporting of Arema Cronus. Arema Cronus also perform social activities as a form of accountability to the community in general.Keywords: Industry, football, management, accountability